Analisis Faktor – Faktor yang Mempengaruhi Minat Pengguna Bike pada Maxim di Kota Semarang - Purnomo Ari Wibowo; Afan Ali Fatah (OPTIMAL Jurnal Ekonomi dan Manajemen, 2025)
This study aims to determine whether the factors of service, price, convenience to the interest of maxim bike users in the city of Semarang. The population in this study is maxim passengers as many as 100 respondents. This research method uses the nonprobablitity sampling method. The sampling technique used in this study is incidental sampling. The analysis technique in this study uses multiple linear regression analysis. The formulation of the regression in this study is as follows: Y = 0.615 + 0.209X1 + 0.287X2 + 0.463X3 + µ Based on statistical results testing with multiple linear regression equations, it was found that the regression coefficient value of the Service Variable (X1) was 0.209 which was positive and the t-count value was 2.601 t- table of 1.98472, the regression coefficient value of Service Variable (X2) was 0.287 which was positive and the value of t count is 3.321 t table is 1.98472, the regression coefficient value of the Ease Variable (X3) is 0.463 which is positive and the t count value is 5.132 t table is 1.98472. The value of the coefficient of determination (Adjusted R Square 55.3%) is obtained which states that the variables Service, Price, Convenience have an influence on User Interest by 55.3%. While other factors that influence user interest (Y) are (100% - 55.3% 44.7%). This means that other factors not examined in this study affect the dependent variable (User Interest) by 44.7%.